2019
DOI: 10.1186/s40942-019-0165-z
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic vitreoretinal surgery: principles, applications and new directions

Abstract: Purpose To analyze endoscopic vitreoretinal surgery principles, applications, challenges and potential technological advances. Background Microendoscopic imaging permits vitreoretinal surgery for tissues that are not visible using operating microscopy ophthalmoscopy. Evolving instrumentation may overcome some limitations of current endoscopic technology. Analysis Transfer of the fine detail in endoscopic vitreoretinal images to extraocular vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 78 publications
0
18
0
Order By: Relevance
“…The console provides a high-resolution camera, xenon-light-based illumination, interfaces for fiberoptic cables, video output, and a treatment laser if needed. [ 13 ] Although this design is very practical, its bulky base unit and high cost, just like the original computer, limit its practicality. Sometimes, the image resolution cannot meet the surgeon's needs.…”
Section: Introductionmentioning
confidence: 99%
“…The console provides a high-resolution camera, xenon-light-based illumination, interfaces for fiberoptic cables, video output, and a treatment laser if needed. [ 13 ] Although this design is very practical, its bulky base unit and high cost, just like the original computer, limit its practicality. Sometimes, the image resolution cannot meet the surgeon's needs.…”
Section: Introductionmentioning
confidence: 99%
“…Optimal visualization of intraocular structures is one of the most important and sometimes challenging aspects of vitreoretinal surgery. When compromised anterior segment transparency or inadequate pupillary dilatation restricts transpupillary observation of the posterior eye segment, an adjunctive skill set of endoscopic vitrectomies can be of help [ 1 , 2 ]. In addition, the endoscope can visualize the ciliary processes, pars plana, and anterior retina without scleral depression, facilitating surgery on these areas without causing peripheral lens aberration or alteration of the normal anatomy from scleral indentation/deformation that are commonly encountered during conventional vitrectomy.…”
Section: Introductionmentioning
confidence: 99%
“…1 Stereopsis, visual details of surgical field, depth of focus and visual field itself are key dependent points of pars plana vitrectomy, and thus the essential requirement for successful and complete Posterior segment surgery is clarity of the ocular media. 2 There are multiple limitations to this which include preexisting cataract that may limit visualization of the retina, the normal clear crystalline lens may limit the removal of peripheral vitreous and traction relieved, and thus it may be more difficult to identify and treat peripheral pathology in phakic eyes. 1 It is important to note that even if there was no visually significant cataract prior to vitrectomy, various studies and clinical experience has shown that these patients will ultimately develop visually significant cataract and will require cataract surgery in future.…”
Section: Introductionmentioning
confidence: 99%